2006
DOI: 10.1177/1356336x06065359
|View full text |Cite
|
Sign up to set email alerts
|

A review of children’s fitness testing

Abstract: A review of literature on children's fitness testing formed part of a study exploring the feasibility of fitness testing children in order to promote their physical activity and health status. The review revealed that there is no empirical evidence to support concerns about low levels of fitness amongst children or a decline in children's fitness over time. Further, there is only weak evidence that physical fitness is related to children's current health although growing evidence that it may be related to futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 51 publications
2
38
0
3
Order By: Relevance
“…In the recent years, there were many scientific works and researches published, particularly by USA authors, elaborating certain problems and issues connected with follow-up of the fitness within the teaching of physical education [24][25][26][27]. One of the most important issues being discussed in these researches is the issue of establishing normative reference that would allow proper assessment, interpretation and comparison of the level of physical fitness of school children in terms of the age, gender, region etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, there were many scientific works and researches published, particularly by USA authors, elaborating certain problems and issues connected with follow-up of the fitness within the teaching of physical education [24][25][26][27]. One of the most important issues being discussed in these researches is the issue of establishing normative reference that would allow proper assessment, interpretation and comparison of the level of physical fitness of school children in terms of the age, gender, region etc.…”
Section: Introductionmentioning
confidence: 99%
“…нормативни референти стандард, у коме су биле дефинисане норме (посебно за дечаке и де-војчице према узрасту) за све компоненте physical tness-a, појављује се критеријумски референт-ни стандард -eng. Criterion-Referenced Standards (Harris, & Cale, 2006). Приликом коришћења нор-ми, теоријски, наставник је могао пратити проме-не у вредностима код неког ученика упоређујући његове резултате са дефинисаним нормама, али добијени резултати нису много говорили о здрав-ственом стању ученика.…”
Section: уводunclassified
“…Within this concept, there are novelties within the referent standard used in batteries of tests for assessment of physical fitness. Unlike earlier batteries of tests that used the so-called normative referenced standard, in which norms were defined (separately for boys and girls according to the age), Criterion-Referenced Standards appear for all components of physical fitness (Harris, & Cale, 2006). While using norms, theoretically, the teacher could monitor changes in values in a student by comparing his results with the defined norms, but the obtained results did not show much about the health condition of a student.…”
Section: Introductionmentioning
confidence: 99%
“…According to the President's Council for Physical Fitness and Sports (PCPFS, 2003), one objective of fitness testing is to encourage and motivate individuals to adopt and adhere to physical activity behaviors across the lifespan. In their review of research related to fitness tests, Harris and Cale (2006) indicated that advocates for fitness tests argued that testing programs increased children's motivation to participate in regular physical activity. Other scholars, however, argued that there had not been sufficient empirical investigation concerning how students experience fitness tests and their motivational implications (Fox & Biddle, 1988).…”
mentioning
confidence: 98%